2001
DOI: 10.1002/1521-3803(20010601)45:3<164::aid-food164>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glycated proteins by mass spectrometric techniques: qualitative and quantitative aspects

Abstract: The analysis of protein glycation poses a difficult challenge due to the complex nature of the reaction. Of the several methods developed for the qualitative and quantitative evaluation of the glycation reaction between proteins and reducing sugars, soft ionization mass spectrometry is the most direct and reliable. In this paper we review the major mass spectrometric methods (ESI and MALDI mass spectrometry) used in the study of protein glycation. We also tested the assumption that limited glycation has little… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…It should be noted that such a method of quantitation can be considered reliable only if the protein ionisation efficiency is not affected by the glycation level. Yeboah and Yaylayan have shown that limited glycation of lyzozyme had little or no effect on the ionisation efficiency of the protein species and also on the charge state distribution 18. Moreover, regarding quantitation of glycoforms, good correlations were obtained between results from ESI‐MS measurements (after spectral deconvolution) with those from alternative quantitative methods using HPLC or UV measurements by Nakanishi et al 19.…”
Section: Resultsmentioning
confidence: 96%
“…It should be noted that such a method of quantitation can be considered reliable only if the protein ionisation efficiency is not affected by the glycation level. Yeboah and Yaylayan have shown that limited glycation of lyzozyme had little or no effect on the ionisation efficiency of the protein species and also on the charge state distribution 18. Moreover, regarding quantitation of glycoforms, good correlations were obtained between results from ESI‐MS measurements (after spectral deconvolution) with those from alternative quantitative methods using HPLC or UV measurements by Nakanishi et al 19.…”
Section: Resultsmentioning
confidence: 96%
“…The level of protein glycation was analyzed according to the method described previously. [15,16] The sample of chemically modified ubiquitin was subjected to enzymatic hydrolysis catalyzed by pepsin. Pepsin is a nonspecific protease, but prefers to hydrolyze peptide bonds at the carboxyl end of Phe and Leu.…”
Section: Resultsmentioning
confidence: 99%
“…Anomalous behavior of glycoproteins has been described before, and the presence of carbohydrates attached to the protein (Segrest et al 1971; Matagne et al 1991) and the tertiary structure of the protein (Rath et al 2009; Pitt-Rivers and Ambesi Impiombato 1968) were shown to influence this behavior. MALDI-TOF-MS is known to provide accurate molecular mass determination of proteins and glycoconjugates (Ledesma-Osuna et al 2008; Yeboah and Yaylayan 2001). …”
Section: Discussionmentioning
confidence: 99%